O real em fuga: negatividade e contingência como prolegômenos lógicos à suposta filosofia política de Hegel - Araújo, Alan Duarte (2023)
This paper seeks to argue that the ontological notions of negativity and contingency act as logical prolegomena indispensable to the general understanding of the speculative philosophy of G.W.F. Hegel (1770-1831), particularly with regard to his writings on social-political issues. The aim is, therefore, to determine the speculative scope of these notions, which, although they do not figure in a precise place in the "grammar" of German Idealism, assume the central role of conceptual beacons that should be understood as a philosophical antechamber for the whole of his doctrine. Thus, negativity stands out as the touchstone of dialectics, in its Hegelian elaboration, which safeguards the critical potential of the underlined method, decentering and weakening concepts and representations hardened by the Understanding (Verstand). Contingency, in turn, assumes a more controversial role in his thought, whose method is not only dialectical, but also speculative, which implies that negation is not exhausted in itself, but engenders a positive and systematic totality, a pole in which chance and the other figures of contingency seem to be excluded a priori, in such a way that, for Hegel, philosophizing implies sustaining the idea that Reason (Vernunft), in its necessary unfolding, governs the world. The apparent disregard for contingency testifies to critics who argue that Hegelianism is afflicted with an insuperable panlogism, and as such is incapable of thinking through the issues concerning earthly reality. In other words, they determine that Hegel would despise the "logic of the thing" in preference to the "thing of logic", upholding a "logic applied" to concrete situations, in this respect, to speak of a Hegelian political philosophy would be nothing more than idealistic nonsense. In response to these questions, the following problem is raised, which guides this research: in speculative philosophy, is there room for a properly political reflection? And here, we conjecture that the solution to this imbroglio lies within the logical-ontological writings of the author, notably in his Science of Logic, even though this answer may seem contradictory. The apparent contradiction tends to dissipate if we follow the guiding thread of the research methodology, which is dialectics, whose goal is to enter into the "Thing itself" (die Sache selbst), not getting lost in opinions and unthinking assumptions, but weaving what the author calls immanent criticism of the works and concepts investigated. The immanence of criticism also justifies the relevance of this research, considering that a large number of critics and even Hegelian commentators tend to decompose his thought, focusing on parts of it, thus obliterating the logical totality of his writings, as well as the prominent role that the concept of contingency plays in his philosophy. Only by running the risk of becoming disoriented in the Gothic architectonics of speculation can we, in attention to the Hegelian grammar, safely assess his theoretical whole. We have chosen, then, to investigate his mature writings, which began after his stay in Iena (1801-1807), the moment when Hegelianism itself acquired its certificate of origin, not forgetting the help of commentators such as Gérard Lebrun (1930-1999), Slavoj Zizek (1949), and Domenico Losurdo (1941-2018), among others. These are the reasons why it is considered more appropriate to "suspend" the status of the supposed Hegelian political philosophy, avoiding making conclusive comments about it, until the research comes to an end and the problematic raised is clarified or dissipated.